Retrospective Multicenter Study Investigating the Role of Targeted Next-Generation Sequencing of Selected Cancer Genes in Mucinous Adenocarcinoma of the Lung. Issue 4 (April 2016) - Righi, Luisella; Vatrano, Simona; Di Nicolantonio, Federica; Massa, Federica; Rossi, Giulio; Cavazza, Alberto; Volante, Marco; Votta, Arianna; Izzo, Stefania; Lo Iacono, Marco; Ardissone, Francesco; Di Maio, Massimo; et al.
ABSTRACT : Introduction: : Mucin‐rich lung adenocarcinomas (ADCs), namely mucinous and colloid ADCs, are classified as ADC variants according to the World Health Organization 2015 classification. A correlation between morphological patterns and mutational status of these rare entities is not well established. Methods: : We investigated the mutational profile of mucin‐rich lung ADCs in correlation with histopathological and morphological features with the goal of identifying biological tumor characteristics of potential prognostic and therapeutic interest. A series of 54 surgically resected primary mucinous lung ADC samples were retrospectively analyzed for clinicopathological characteristics and by targeted next‐generation sequencing. Results: : Fifty cases were invasive mucinous ADCs (32 pure and 18 mixed) and four were colloid‐predominant ADCs. Invasive mucinous ADC cases with a pure mucinous pattern were associated with a lower risk of vascular invasion ( p = 0.01), absence of signet ring cells ( p = 0.03), negative nodal status ( p = 0.006), and early clinical stage ( p = 0.02). The most prevalent mutations involved the Kirsten rat sarcoma viral oncogene homolog gene ( KRAS ) and tumor protein p53 gene ( TP53 ). Most mutations clustered in the mitogen‐activated protein/protein kinase B pathway and in the p53/DNA repair pathway. A few uncommon epidermal growth factor receptor gene ( EGFR ) mutations were found. A correlation between a higher number of mutations and favorable clinical outcome was seen ( p < 0.001). Conclusions: : Our data showed that mucinous ADCs have peculiar pathological and molecular features that might suggest the need for a differentially tailored therapeutic approach compared with that to conventional lung ADC.